2016
DOI: 10.1016/j.fuel.2016.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability study of NiAl2O4 binders for Chemical Looping Combustion application

Abstract: The influence of the preparation method of NiAl 2 O 4 binders on their thermal stability was studied. For this purpose, the reactivity of two different NiAl 2 O 4 binders with CO as fuel was studied in a fixed bed reactor device. Successive oxidation-reduction cycles were performed-2/19-on the two binders to study their reactivity with the fuel and their structural modifications as cycles proceed. Results reveal that binders are not inert in reducing atmosphere; they both react with the fuel to produce CO 2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
1
9
0
1
Order By: Relevance
“…To observe the temperature influence, experimental tests should be performed at high flow rates (i.e., with immediate percolation of the combustible gas). At the same time, the increase of overall oxidized CO with temperature is certainly due to the separation of the binder (NiAl 2 O 4 ) phase to NiO and Al 2 O 3 , as previously observed [11]. …”
Section: Reactor and Oxygen Carrier Operating Conditionssupporting
confidence: 81%
See 1 more Smart Citation
“…To observe the temperature influence, experimental tests should be performed at high flow rates (i.e., with immediate percolation of the combustible gas). At the same time, the increase of overall oxidized CO with temperature is certainly due to the separation of the binder (NiAl 2 O 4 ) phase to NiO and Al 2 O 3 , as previously observed [11]. …”
Section: Reactor and Oxygen Carrier Operating Conditionssupporting
confidence: 81%
“…For these different reasons, this OC was widely used in laboratory studies. However, previous studies showed that the binder can react with fuel and lose partly its properties [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the high value utilization of biomass pyrolysis gas is promising and urgent. At present, several technologies were considered as potential options for improving the value of biomass pyrolysis gas, such as chemical looping re-forming (CLR), steam re-forming, and so on. , CLR is a competitive option to produce H 2 as well as capturing CO 2 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 CLR is a competitive option to produce H 2 as well as capturing CO 2 . 3 Moreover, oxygen carriers (OCs) are one of the most important factors in the CLR; in particular, the supplied oxygen properties of OCs such as supplied oxygen content, supplied oxygen rate, and supplied oxygen temperature were the key point for improving the effectivity during the CLR. 4 However, research about the supplied oxygen properties is rare.…”
Section: ■ Introductionmentioning
confidence: 99%
“…80 At high temperature, the Ni support with alumina formed the NiAl 2 O 4 spinel compound. 81 The spinel compound has a strong interaction with an alumina support that cannot take part in reductive and oxidative reactions. This causes loss of Ni contents in the OC after a few redox cycles.…”
Section: Oxygen Transport Capacity Of Variousmentioning
confidence: 99%